2017
DOI: 10.1155/2017/2879249
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetic Foot Ulcer and Associated Factors among Adult Diabetic Patients Who Attend the Diabetic Follow-Up Clinic at the University of Gondar Referral Hospital, North West Ethiopia, 2016: Institutional-Based Cross-Sectional Study

Abstract: Diabetes mellitus is a metabolic disorder which is characterized by multiple long-term complications that affect almost every system in the body. Foot ulcers are one of the main complications of diabetes mellitus. However, there is limited evidence on the occurrence of foot ulcer and influencing factors in Ethiopia. An institutional-based cross-sectional study was conducted in Gondar University Hospital, Ethiopia, to investigate foot ulcer occurrence in diabetic patients. Systematic random sampling was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
143
5
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(207 citation statements)
references
References 9 publications
33
143
5
16
Order By: Relevance
“…8, 44.4). This result is consistent with prior studies [19,27].This association is possibly because DPN promotes ulcer formation by causing loss of protective pain sensation, loss of pressure perception, and impairment of microcirculation [32,33]. Journal of Diabetes Research Furthermore, according to the current finding, participants who had a history of foot ulceration were 5.77 times more likely to develop diabetic foot ulcer than those without a previous history of foot ulceration (AOR = 5:77; 95% CI: 2.37, 14).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…8, 44.4). This result is consistent with prior studies [19,27].This association is possibly because DPN promotes ulcer formation by causing loss of protective pain sensation, loss of pressure perception, and impairment of microcirculation [32,33]. Journal of Diabetes Research Furthermore, according to the current finding, participants who had a history of foot ulceration were 5.77 times more likely to develop diabetic foot ulcer than those without a previous history of foot ulceration (AOR = 5:77; 95% CI: 2.37, 14).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the prevalence of diabetic foot ulcers among diabetic patients attending JMC was 11.6% (95% CI: 7.9, 15.5). This finding is in line with three independent studies done in Ethiopia, 13.6% in Gondar, 12% in Mekelle, and 14.8% in Arbaminch [19,22,23]. In addition, similar finding in North India (14.3%) and in Tanzania (15%) [24,25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Diabetes-related lower limb ulcers are a leading cause of global morbidity, mortality and rising healthcare costs [1][2][3]. Such ulcers often become chronic, are associated with reduced health-related quality of life, and are frequently a prelude to infection, hospital admission and amputation [1][2][3][4][5][6][7][8][9][10]. Establishing better ways to treat diabetes-related lower limb ulcers is a global priority [2].…”
Section: Introductionmentioning
confidence: 99%
“…Also, hyperbaric oxygen therapy, electrical stimulation, pessimistic pressure wound therapy, technological skin and growth factors could be used as an adjunct therapy for quick healing of diabetic foot ulcer. So, it's suggested that with appropriate patient education encourages them to regular foot care in order to prevent diabetic foot ulcer and its complications (Mariam et al, 2016;Benotmane et al, 2015) . The rate of lower limb amputation in patients with DM is 15 times higher than patients without diabetes it is estimated that approximately 50% to 70% of all lower limb amputation are due to diabetic foot ulcer in addition it is reported than every 30's one legist amputated due to diabetic foot ulcer in worldwide furthermore diabetic foot ulcer is responsible for substantial emotional and physical distress, as well as productivity and inancial, lose that over the quality of life (Shankhdhar et al, 2016;Cerf et al, 2015;Singh and Pal, 2008) .…”
Section: Introductionmentioning
confidence: 99%